Transforming women’s and providers’ experience of care for improved outcomes: A theory of change for group antenatal care in Kenya and Nigeria - Grenier, Lindsay; Onguti, Brenda; Whiting-Collins, Lillian J.; Omanga, Eunice; Suhowatsky, Stephanie; Winch, Peter J. (PloS one, 2022)
Group antenatal care (G-ANC) is a promising model for improving quality of maternal care and outcomes in low- and middle-income countries (LMICs) but little has been published examining the mechanisms by which it may contribute to those improvements. Substantial interplay can be expected between pregnant women and providers' respective experiences of care, but most studies report findings separately. This study explores the experience and effects of G-ANC on both women and providers to inform an integrated theory of change for G-ANC in LMICs. This paper reports on multiple secondary outcomes from a pragmatic cluster randomized controlled trial of group antenatal care in Kenya and Nigeria conducted from October 2016-November 2018 including 20 clusters per country. We collected qualitative data from providers and women providing or receiving group antenatal care via focus group discussions (19 with women; 4 with providers) and semi-structured interviews (42 with women; 4 with providers). Quantitative data were collected via surveys administered to 1) providers in the intervention arm at enrollment and after facilitating 4 cohorts and 2) women in both study arms at enrollment; 3-6 weeks postpartum; and 1 year postpartum. Through an iterative approach with framework analysis, we explored the interactions of voiced experience and perceived effects of care and placed them relationally within a theory of change. Selected variables from baseline and final surveys were analyzed to examine applicability of the theory to all study participants. Findings support seven inter-related themes. Three themes relate to the shared experience of care of women and providers: forming supportive relationships and open communication; becoming empowered partners in learning and care; and providing and receiving meaningful clinical services and information. Four themes relate to effects of that experience, which are not universally shared: self-reinforcing cycles of more and better care; linked improvements in health knowledge, confidence, and healthy behaviors; improved communication, support, and care beyond G-ANC meetings; and motivation to continue providing G-ANC. Together these themes map to a theory of change which centers the shared experience of care for women and providers among multiple pathways to improved outcomes. The reported experience and effects of G-ANC on women and providers are consistent with other studies in LMICs. This study is novel because it uses the themes to present a theory of change for G-ANC in low-resource settings. It is useful for G-ANC implementation to inform model development, test adaptations, and continue exploring mechanisms of action in future research.